Para além da geração de renda: os significados da fruticultura para os agricultores familiares de Santa Helena – PR - Klesener, Hedson Mauro (2020)
Faced with a scenario in which family farming is increasingly undergoing profound changes in production, technology and access to markets, the need to carry out studies aimed at family farmers, in search of other strategies for the permanence of these workers in the rural environment with work and decent income. The present study was carried out in the municipality of Santa Helena - PR and had as its central theme the production of fruit by family farmers. Some issues around it were addressed, such as Sustainable Rural Development, family farming, diversification in rural areas, rural succession, markets, fruit growing, public policies and quality of life. The main objectives that drove this research were to identify and understand the reasons that motivate family farmers to practice fruit production, as well as the reasons and reasons that hinder or prevent them from working with this activity. To obtain the success of these objectives, the research took place primarily in bibliographic and documentary literature, where it sought to understand the view of several researchers regarding the studied themes, whose helped in the definition of the theme and in the delimitation of the study, objectives and methodology used. In the documental literature, we searched for information and data covered in existing research and information, such as the production database of SAEP / DERAL and IBGE, as well as data from research carried out at the Advanced Research Center - CAP, located in the municipality of Santa Helena-PR. As for empirical research, semi-structured interviews were conducted, with questions focused on the proposed theme, with 21 families of family farmers, of these 12 who practice fruit production and the rest who do not practice this activity. Thus, it was possible to understand several reasons that motivate some family farmers to practice fruit production and also the reasons that lead others not to adhere to this practice. The reasons highlighted by the interviewees who produce fruit are not limited to financial issues and, for these families, this activity represents meanings that corroborates the notion of sustainable rural development.